Are Western Australian adolescents keen book readers? - Merga, Margaret (Australian Literacy Educators' Association, 2014)
As book reading offers significant benefit for adolescents, a current understanding of whether or not Western Australian adolescents are keen recreational book readers is important for literacy educators and policy makers. This article considers the findings of a study exploring the engagement in recreational book reading of Year 8 and Year 10 students in 20 Western Australian schools in Term 4 of 2012. The article reflects on the frequency and volume of recreational book reading, as well as current attitudes toward recreational book reading in this cohort. The findings of this study suggest that the majority of Western Australian adolescents may not be keen book readers, and that boys may read less, and have a less positive attitude toward book reading, than girls.